Sexting and behavioral health in first-time justice-involved adolescents. (January 2022) - Ng, Mei Yi; Harrison, Anna; Bath, Eraka; Kemp, Kathleen; Galbraith, Katharine; Brown, Larry K.; Tolou-Shams, Marina
Highlights: Over one-third of first-time justice-involved adolescents reported sexting. Past-year sexting was associated with engaging in unprotected sex, delinquent acts, and substance use. Past-year sexting was associated with elevated trauma and internalizing symptoms. Assessing sexting could inform intervention, but local laws should be considered. Abstract: Objective(s): We examined the prevalence of sexting, related motivations, demographics, and association with behavioral health problems among justice-involved adolescents. Hypotheses: We hypothesized positive associations between sexting and sexual risk, substance use, delinquency, and mental health problems. Methods: Participants were 307 community-supervised justice-involved adolescents with a first-time offense (Mage = 14.50 years, 44.6% female) and their caregivers. Adolescents answered questions on technology use and sexting by sending, receiving, or forwarding sexually suggestive text messages and images (pictures or videos). They also completed measures of recent (past 4-month) sexual activity, unprotected sex, cigarette, alcohol, marijuana, and other drug use, and delinquency; current trauma symptoms, internalizing problems, and adaptive functioning. Results: Prevalence of sexting were 37.7% (lifetime overall; 17.0% sent texts; 17.4% sent images) and 29.5% (past-year overall; 12.8% sent texts; 13.6% sent images). Sexts were commonly sent as presents to partners, in response to sexts received, or to have fun. "Sexters" were older than "non-sexters" and more likely to identify as lesbian, gay, bisexual, or questioning. Past-year sexting was significantly associated with recent sexual activity; unprotected sex; alcohol use and days of use; marijuana and other drug use; delinquency and variety of delinquent acts; and elevated trauma symptoms and internalizing problems. Conclusions: Sexting is prevalent among adolescents with a first-time offense and co-occurs with multiple behavioral health needs. Intervention for this population may be informed by routinely assessing sexting in community settings. Familiarity with local reporting laws could help clinicians navigate the legal implications of sexting among adolescents with existing justice-system involvement.